Syncope Associated with Subthalamic Nucleus Deep Brain Stimulation in a Patient with Parkinson's Disease. (22nd December 2013) - Aygun, Dursun; Kocabicak, Ersoy; Yildiz, Onur; Onar, Musa Kazim; Guz, Hatice; Boke, Omer; Kurt, Murat; Temel, Yasin
Abstract : In advanced Parkinson's disease (PD), deep brain stimulation (DBS) may be an alternative option for the treatment of motor symptoms. Side effects associated with subthalamic nucleus (STN) DBS in patients with PD are emerging as the most frequent sensory and motor symptoms. DBS-related syncope is reported as extremely rare. We wanted to discuss the mechanisms of syncope associated with STN DBS in a patient with Parkinson's disease. Case report. Sixty-three-year-old female patient is followed up with diagnosis of idiopathic Parkinson's disease for 6 years in our clinic. The patient has undergone STN DBS due to painful dystonia and drug resistant tremor. During the operation, when the left STN was stimulated at 5 milliampere (mAmp), the patient developed presyncopal symptoms. However, when the stimulation was stopped symptoms improved. During the early period after the operation, when the right STN was stimulated at 1.3 millivolts (mV), she developed the pre-yncopal symptoms and then syncope. Our case shows that STN DBS may lead to directly autonomic symptoms resulting in syncope during stimulation-on (stim-on).